Skeletal remains from South Swedish Late Neolithic - Early Bronze Age - Tornberg, Anna (University1, 2018)
The database is the foundation for a study of health in Late Neolithic-Early Bronze Age southern Sweden. Skeletal remains from 46 loclities have been osteologically registered. The database founded studies of paleopathology, paleodemography and stature.

Purpose:

Database for the study of health in Late Neolithic-Early Bronze Age Southern Sweden. Data for PhD dissertation in historical osteology.

Osteological registration. Ocular assessment.

Databasen ligger till grund för studien av hälsa i senneolitikum och äldre bronsålder i Sydsverige. Skelettmaterial har osteologiskt registrerats från 46 olika lokaler. Databasen har legat till grund för paleopatologi, paleodemografi och kroppslängdsstudier.

Syfte:

Databas för studie av hälsa i senneolitikum och äldre bronsålder. Underlag för doktorsavhandling i historisk osteologi.

Osteologisk registrering. Okulär bedömning.
Skelettmaterial från senneolitikum - äldre bronsålder i Sydsverige
Keywords: Late Neolithic; senneolitikum; Early Bronze Age; äldre bronsålder; skeleton; skelett; osteology; osteologi; health; hälsa; HISTORY; HISTORIA; Humanities and the Arts; Humaniora och konst